2020
DOI: 10.1155/2020/6167234
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multidrug-Resistant and Extended-Spectrumβ-Lactamase-Producing Enterobacteriaceae: A Cross-Sectional Study at Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia

Abstract: Background. Multidrug-resistant Enterobacteriaceae particularly extended-spectrum beta-lactamase producers have become a major public health threat. Despite efforts to limit their spread, rates of multidrug-resistance members of the Enterobacteriaceae continue to increase throughout the world causing increased morbidity and mortality and raised costs for medical care. Objective. The aim of this study was to determine the prevalence of multidrug resistance and extended-spectrum β-lactamase-producing Enterobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
10
25
0
Order By: Relevance
“…The variation might be due to the study population, the number of isolates assessed, the technique utilized, etc. However, our study findings are in line with the study conducted at Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia by Bitew et al 42.1%[21]. The dominant MDR isolates were K. Pneumoniae 80(73.4%) however our result disagrees with study findings of Beyene et al in which E. coli (99.3%…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The variation might be due to the study population, the number of isolates assessed, the technique utilized, etc. However, our study findings are in line with the study conducted at Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia by Bitew et al 42.1%[21]. The dominant MDR isolates were K. Pneumoniae 80(73.4%) however our result disagrees with study findings of Beyene et al in which E. coli (99.3%…”
supporting
confidence: 55%
“…In the present study, the prevalence of XDR gram-negative bacilli was 7.7% [33/429], which is slightly lower than study at Ethiopian Public Health Institute, Ethiopia by Beyene et al 8.8% [19] the variation might be due to the fact the investigators analyzed only Enterobacterales, much lower than the findings from the study at Jimma, Ethiopia by Gashaw et al 41.3% [20], Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia by Bitew et al 34.3% [21], Tertiary Care Hospital, Pakistan by Abbas et al 64% [22]. The variation might be due to geographic location, the technique utilized, XDR definition, types of organism, etc.…”
Section: Discussionmentioning
confidence: 79%
“…These reports are in accordance with our results on the most common bacterial isolation and ESBL activity, with a slight variation in MDR prevalence among the two bacteria. A study from Addis Ababa reported a 42.1% MDR among Enterobacteriaceae [ 30 ]; however, another recent study from Saudi Arabia reported an overall prevalence of 60% MDR Enterobacteriaceae , with E. coli and K. pneumoniae as the most frequent isolates [ 31 ], but this prevalence was only 6.6% in the USA hospitals [ 32 ]. The analysis adopted in the present study revealed higher MDR prevalence, and this prevalence was determined for the three predominant bacteria and not for all Enterobacterales isolates reported during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Still, its importance is often underestimated in community infections, as hospitalized infections gain the most attention [2]. Many previous studies have addressed the prevalence of AR in clinical environments [3][4][5], and more recently AR prevalence in non-hospitalized populations too [6,7]. Most of these studies were conducted on cultivable clinical strains using microbiological methods that involve cultivation and antibiogram tests.…”
Section: Introductionmentioning
confidence: 99%